ANALISIS KEBIJAKAN PENYEDERHANAAN BIROKRASI PEMERINTAH DAERAH - Rusliandy Rusliandy (Department of Public Administration, Muhammadiyah University of Makassar, 2022)
The purpose of this study is to analyze the policy of simplifying the bureaucracy for local governments including the analysis of organizational transformation, transformation of positions and transformation of performance management. The research method used is descriptive qualitative. The results show that the implementation of bureaucratic simplification is faced with several things: (1) organizational design has not been designed to accommodate the performance of functional positions (2) functional position management is not yet professional in some coaching agencies, types of functional positions that are not yet available, competency gaps, and patterns of relationship governance. not optimal work. (3) individual performance appraisal has not been aligned with organizational performance. Strategies that must be carried out to support the effectiveness of bureaucratic simplification include: (1) adopting the professional bureaucracy model by improving the weaknesses of PP 18 of 2016. (2) developing the competence of functional officials, as well as improving the quality of functional office management, (3) Creating management policies performance that can measure individual performance appraisals in line with organizational performance, and leads to high-performing organizations.